Reiteration frequency of immunoglobulin light chain genes: further evidence for somatic generation of antibody diversity. - Tonegawa, S (1976)
Methods have been developed for preparing mouse immunoglobulin light chain mRNA of better than 90% purity. Hybridization of both lambda and kappa mRNAs to excess liver DNA yielded results compatible with gene reiteration frequencies of two to three. There was no evidence of hybridization of these highly purified mRNAs to reiterated DNA, and, in fact, the kinetics of hybridization were very similar to that of purified globin mRNA. Purified lambda mRNA from tumors producing structurally different lambda chains were used in competition hybridization experiments. An unlabeled lambda mRNA competed with another, labeled lambda mRNA to the same extent as homologous unlabeled lambda mRNA. That is, base sequence homology among lambda mRNAs is so high that any lambda mRNA should cross-hybridize with all germ line variable (Vlambda) genes at least for those V-regions which are represented among myelomas. From amino-acid sequence data, it is argued that there are probably more than 25 different lambda V regions. Hence it is concluded that the number of germ line genes is too small to account for the diversity of lambda chains. A similar conclusion is drawn for kappa chains.